(untitled) (Fiep Bulletin - online, 2014)
This paper occur the use of technologies of information and communication (ICTs) in class of informatics in schools municipals of Florianópolis, SC, Brasil. The research identifies the relation of ICTs with the process of teaching-knowledge questioning the practice pedagogic of teachers, especially of Physical Education. The design of exploratory study found some answers by analyzing documents, in interviews with coordinators of technological class and significant bibliography revision. The study found that the discipline of Physical Education, although of changes provokes for ICTs in Education, is limited the same methodologies outdates. Found out many aspects that contributes to this situation, for example: lack of capacity from teachers and the need of interdisciplinary proposal, especially which the use the technologies such as pedagogical instrument. This study offers a contribution to the quality of Physical Education in schools.